5 Yearsʼ Experience of a Tertiary Center with Thrombocytopenic Pregnancies: Gestational Thrombocytopenia, Idiopathic Thrombocytopenic Purpura and Hypertensive Disorders of Pregnancy - Fadiloglu, Erdem; Unal, Canan; Tanacan, Atakan; Portakal, Oytun; Beksac, Mehmet Sinan (Geburtshilfe und Frauenheilkunde, 2020)
Aim To evaluate thrombocytopenic pregnancies including gestational thrombocytopenia (GT), idiopathic thrombocytopenic purpura (ITP), and hypertensive disorders of pregnancy (HDP).Materials and Methods We evaluated the pregnancy outcomes and laboratory findings of 385 patients diagnosed with GT, ITP, or HDP whose thrombocyte levels were < 150 000/µL.Results GT, ITP, and HDP were the final diagnoses in 315 (81.8%), 35 (9.1%), and 35 (9.1%) cases, respectively. Patients diagnosed during the 1st trimester and diagnosed with ITP had significantly lower minimal platelet counts during the antenatal period and prior to delivery (p < 0.001; p < 0.001; p < 0.001; p < 0.001). Transfusion of any kind of blood product was given in 9.9% (n = 38) of all cases. Twelve patients had methylprednisolone and/or intravenous immunoglobulin treatments during the antenatal period. All patients who had undergone medical treatment were also found to have ITP. Four out of 385 patients underwent hysterectomy post partum due to refractory hemorrhage. Analysis of newborn platelet levels showed no statistical differences between any of the groups. Despite the lack of statistical significance, the rate of thrombocytopenia in newborns was 50% in patients with severe thrombocytopenia, while rates were 25.6 and 18.1% in patients with moderate and mild thrombocytopenia, respectively.Conclusion Thrombocytopenic pregnancies must be carefully evaluated with regard to the severity of thrombocytopenia, gestational period at initial diagnosis, and etiology. In particular, patients with ITP must be evaluated carefully as these patients are more likely to require transfusions and have platelet counts < 50 × 103/µl.
Keywords: pregnancy; gestational thrombocytopenia; idiopathic thrombocytopenic purpura; hypertensive disorders of pregnancy